STRATEGI INDONESIA MENANGANI PERDAGANGAN MANUSIA DI JALUR PERBATASAN INDONESIA-MALAYSIA (STUDI KASUS: PERDAGANGAN MANUSIA DI KABUPATEN BENGKALIS TAHUN 2017-2018) - Novrecha Wiliza; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
A strategy is a way or a stage of plans and actions to achieve an outcome, be it a goal or a system to achieve it. The focus is related to the issue of human trafficking in the Bengkalis district borders in 2017-2018.This type of research is used by the author with qualitative research methods, namely research procedures that produce descriptive data and study by going to the field. The data collection technique is done by using literature study and field study methods. Researchers use books, journals, electronic media, interviews, and various sources that support the research process including those directly involved in the field. The author uses level of nation-state analysis, by using security theory.This research shows that there are various strategies implemented to handle cases of human trafficking in Indonesia’s border areas. The handling strategy also refers to the central strategy of the government and including with international cooperation.Keywords: Strategy, Human Trafficking, Borders, Cooperation.